Europeanisation of aid budgets: nothing is as it seems. Issue 1 (2nd January 2016) - Delputte, Sarah; Lannoo, Steven; Orbie, Jan; Verschaeve, Joren
ABSTRACT: In 2002 the European Union (EU) decided to gradually increase its official development assistance (ODA) towards the '0.7% norm' by 2015. Both in terms of policy and in terms of procedures, this constituted a remarkable integrationist shift in EU development policy. However, it is unclear to what extent this integrationist shift (bottom-up) has effectively enhanced the EU's influence over its member states (top-down). More than 13 years after the EU's explicit goal to Europeanise the ODA issue, this article aims to assess to what extent it has been successful. More specifically, it analyses the impact of the EU's '0.7% norm' on the national aid budgets. Through an inductive analysis involving 15 member states over a large time span, a comprehensive assessment of Europeanisation is provided. The conclusion reads that nothing is like it seems: ostensible compliance with EU targets appears mostly unrelated to the EU, while the EU might have contributed to non-compliance.